Effect of Metarhizium robertsii Associated with Lufenuron on the Mortality of Nezara viridula (Hemiptera: Pentatomidae) - Ferreira-Agüero, Marcos Arturo; Oliveira Janeiro Neves , Pedro Manuel; Gimenez Cremonez , Paulo Sergio; Marquez Fernández , Diego Manuel (Revista Colombiana de Entomología, 2023)
The compatibility, pathogenicity, efficiency, and interaction of Metarhizium robertsii (formerly M. anisopliae) with lufenuron on Nezara viridula control were evaluated. Two bioassays were conducted in the laboratory. The first bioassay tested the effect of two concentrations of lufenuron on germination, colony forming units (CFU), vegetative growth and conidia production of M. robertsii. In the second bioassay, the pathogenicity through lethal concentrations (LC) and lethal time (LT) on M. robertsii as well as their efficiency and interaction associated with lufenuron on the mortality of N. viridula was determined. The results indicate that M. robertsii and lufenuron, in lower concentrations are compatible, however, high concentrations of the insecticide may reduce the germination and CFU number. Higher concentrations of M. robertsii increase the percentage mortality of N. viridula nymphs and reduce the lethal time. The interactions of M. robertsii with lufenuron are efficient with additive effects and show potential for use in integrated management of N. viridula nymphs.